A one-mode-for-all predictor for text messaging - Balakrishnan, Vimala; Sim, Foo Guan; Raj, Ram Gopal (Maejo University, 2011)
This paper discusses the enhancements made on the current mobile phone messaging software, namely the predictive text entry. In addition, the application also has a facility to abbreviate any unabbreviated words that exist in the dictionary, so that the message length can be reduced. The application was tested in a computer-simulated mobile environment and the results of the tests are presented here. These additional features will potentially enable users to send messages at a reduced length and thus reduce the cost of sending messages. Moreover, users who are not adept in using the abbreviations can now do so with features made available on their mobile phones. It is believed that these additional features will also encourage more users to use the predictive software as well as further improve usersâ messaging satisfaction